Protection of Online Gender-Based Violence Victims: A Feminist Legal Analysis - Violin, Gisela; Nafi, Yvonne Kezia (The Indonesian Journal of Socio-Legal Studies, 2022)
The complexity of the digital era, especially throughout the COVID-19 pandemic, has led to increasing cases of gender-based violence online (GBVO). However, this issue has not yet received attention in the realm of Indonesian law, especially when it comes to protecting the rights of the victims. This paper aims to see how the current legal framework in Indonesia handles GBVO cases and whether it is sufficient to provide protection for victims. This paper also wants to show that the practice of GBVO is often more detrimental to women through the elaboration of several examples of cases that are widely discussed in Indonesian society. The correlation between the strong patriarchal culture; and the lack of understanding by the community and law enforcement officers on the concept of consent always corners women as victims of GBVO and applies it to the secondary victimization process. The research was conducted using a feminist legal method that focuses on the experience of women as victims to encourage the formulation of a legal umbrella and legal system with a more victim perspective.